COLLAGE QUALITY OF BRAZILIAN WOODS FOR USE IN GLUED LAMINATED TIMBER BEAMS - Molina, Julio Cesar (2023)
The glued laminated timber industries in Brazil have been looking for alternatives that improve the quality of their products, by choosing the correct wood used in the composition of the structural elements, type of adhesive, as well as by monitoring the quality of the material's manufacturing process. This study evaluated the percentage of delamination and shear strength of glue lines in glulam beams constructed with Brazilian reforestation woods (pine and eucalyptus) and structural adhesives (Cascophen RS 216M and Polyurethane Jowat 686.60). For that, the Brazilian test method [1] based on the [2] was used. To qualify the percentage of failure in the gluing areas, the ImageJ software was used. Complementary microscopy analyzes were used to evaluate the gluing areas. As a result, it was observed that the best bonding quality results were obtained for pine and eucalyptus woods bonded with Cascophen RS 216M adhesive. There were no statistically significant differences between the shear strengths of the glue lines of the cross sections of the tested beams. The wood density and the adhesive viscosity had an influence on the bonding quality of glulam beams. The microscopic analyzes indicated that pine woods have an anatomical structure that allows better bonding quality.